2021
DOI: 10.3389/fpsyt.2021.661807
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy for Unmedicated Obsessive-Compulsive Disorder: A Randomized Controlled Trial With 6-Month Follow-Up

Abstract: Background: This was the first randomized controlled trial (RCT) designed to compare the efficacy of mindfulness-based cognitive therapy (MBCT) on unmedicated obsessive-compulsive disorder with that of the first-line treatment for OCD (SSRIs) or a placebo, as well as to analyze the treatment acceptability and safety of MBCT.Methods: A total of 123 unmedicated OCD patients with mild to moderate symptoms were randomly assigned into selective serotonin reuptake inhibitors group (SSRIs group), MBCT group or psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Only four of the included studies (15.4%) reported on the presence or absence of adverse effects. Of these, three (75%) reported no adverse effects (Strauss et al, 2018, Wilhelm et al, 2014; Zhang et al, 2021), and one (25%) reported exacerbated depression in two participants, one in each of the two treatment groups (Rupp et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Only four of the included studies (15.4%) reported on the presence or absence of adverse effects. Of these, three (75%) reported no adverse effects (Strauss et al, 2018, Wilhelm et al, 2014; Zhang et al, 2021), and one (25%) reported exacerbated depression in two participants, one in each of the two treatment groups (Rupp et al, 2019).…”
Section: Resultsmentioning
confidence: 99%